SYNERGETIC APPROACH TO THE ANALYSIS OF THE DYNAMICS OF THE POPULATION OF THE MUSBERRY POPULATION IN THE CONDITIONS OF THE ARAL REGION - Alimova S. Z.; Mambetullaeva S. M. (American Journals Publishing, 2023)
The article discusses the results of a synergistic approach to the analysis of the dynamics of the muskrat population in the conditions of the Aral Sea region. The destabilization of the ecosystems of the Southern Aral Sea, in particular, the violation of the hydro regime, one way or another, affects the population of the muskrat. Under the influence of permanent or temporary action of various external perturbations in a non-equilibrium state, detailed equilibrium does not exist.
Keywords: environmental conditions, Aral Sea region, population dynamics, population, stability.